Design and fabrication of a solid rocket motor - Wan Nursyazwani, Ibrahim (2013)
Rocket have been used from as early as the thirteenth century as fireworks and weapon. However, since then the usage of the rocket have been diversified. Nowadays, rocket are used from a as small as model rocketery for hobbyist to as large as a satelite launcher. Another diversified usages of rocket is as a launch vehicle for cloud seeding. This thesis examines the theoritical performance of a solid rocket motor which developed for launching small amteur research rockets. The theoritical results are presented in the form of fabrication two different throat size of nozzle, bulkhead and motor casing. Actual testing of the motor is performed utilizing a specially designed test rig in order to compare the result. As well, optimization of the motor's performance is investigate. The theoritical performance is found to be in good agreement with the test results, providing a basis for future design of larger engines.